Download presentation
Presentation is loading. Please wait.
Published byMerry Gilbert Modified over 9 years ago
2
FACTORING a polynomial means to break it apart into its prime factors. For example: x 2 – 4 = (x + 2)(x – 2) x 2 + 6x + 5 = (x + 1)(x + 5) 3y 2 + 10y – 8 = (3y – 2)(y + 4)
4
Let’s begin by grouping the first two terms and the last two terms: (ax + ay) + (bx + by) Next, factor out the GCF of each group: a(x + y) + b(x + y) Notice that (x + y) is a common factor of each term. This means: ◦ ax + ay + bx + by = (x + y)(a + b)
5
First, group each set of terms: (x 3 + 7x 2 ) + (2x + 14) Then, take out GCFs: x 2 (x + 7) + 2(x + 7) Write final answer: (x + 7)(x 2 + 2)
6
First, group each set of terms: (3x 2 + xy) – (12x + 4y) Notice that because there was a minus here, we needed to change the sign in our second group! Then, take out GCFs: x(3x + y) – 4(3x + y) Write final answer: (3x + y)(x – 4)
7
1. a 3 – 2a 2 + 5a – 10 2. 15y 3 + 24y 2 – 35y – 56
8
Answer: (a – 2)(a 2 + 5) Answer: (5y + 8)(3y 2 – 7) 1. a 3 – 2a 2 + 5a – 10 Group: (a 3 – 2a 2 ) + (5a – 10) GCFs: a 2 (a – 2) + 5(a – 2) 2. 15y 3 + 24y 2 – 35y – 56 Group:(15y 3 + 24y 2 ) – (35y + 56) **Notice the sign change! GCFs: 3y 2 (5y + 8) – 7(5y + 8)
10
First, remember that your equation must be set equal to 0 before factoring. 3x 2 + 2x – 5 = 0 There isn’t a GCF to factor out. So, factor. (3x + 5)(x – 1) = 0 Next, using the Zero Product Property, set each factor equal to 0 and solve for x. 3x + 5 = 0 or x – 1 = 0 x = -5/3 or x = 1 The solution set is: Note the graph shows us 2 zeros, so our solution makes sense!
12
These three terms have a GCF that we will need to factor out first: 2x 3 (2x 2 – 3x – 2) = 0 Then, factor: 2x 3 (2x + 1)(x – 2) = 0 Set each factor equal to 0: 2x 3 = 0 or 2x + 1 = 0 or x – 2 = 0 Solve for x: Note the graph shows us 3 zeros, so our solution makes sense!
13
First, we need to set our equation equal to 0: 3x 4 – 4x 2 + 1 = 0 Then, factor: (3x 2 – 1)(x 2 – 1) = 0 Set each factor equal to 0: 3x 2 – 1 = 0 or x 2 – 1 = 0 Solve for x: Note the graph shows us 4 zeros, so our solution makes sense!
14
First, factor: (x 2 + 1)(x 2 – 1) = 0 (x 2 + 1)(x + 1)(x – 1) = 0 Set each factor equal to 0: x 2 + 1 = 0 or x + 1 = 0 or x – 1 = 0 Solve for x: Note the graph shows us 2 zeros, because our calculator only shows REAL zeros.
16
A company sells an item for x dollars. Their revenue y (in dollars) is given by the polynomial equation y = -10x 4 + 1000x 2. At what price will the company stop making money?
17
Look at the graph of the function first: We want to find the zeros, because then we will know when the company isn’t making any money (revenue of $0). We can factor the polynomial equation to find these zeros!!!
18
Let’s factor 0 = -10x 2 (x 2 – 100) 0 = -10x 2 (x + 10)(x – 10) Now set each factor equal to 0 and solve for x: -10x 2 = 0 or x + 10 = 0 or x – 10 = 0 -10 doesn’t make sense in the situation because the company wouldn’t charge -$10 0 doesn’t make sense in the situation because the company wouldn’t charge $0 10 does make sense! If the company charges $10, they won’t make any money…this would most likely be because people wouldn’t spend that much money for the item.
Similar presentations
© 2025 SlidePlayer.com. Inc.
All rights reserved.